Responses of soil aggregate characteristics to grazing intensity differ between topsoil and subsoil in a typical steppe - Li, Hao; Yang, Zeyu; Guo, Xiao; Li, Hangyu; Li, Xing; Wu, Yantao; Han, Ying; Li, Zhiyong; Zhang, Jinghui; Miao, Bailing; Liang, Cunzhu (Frontiers in Environmental Science, 2025)
Soil aggregates are vital to soil structure, influencing grassland ecosystem health and sustainability. As a dominant land use in grasslands, grazing acts as a key driver of ecosystem structure and function, yet the responses of aggregate size distribution and stability to grazing intensity across soil depths remain insufficiently understood. Here, we conducted an eight-year sheep grazing experiment in a semi-arid steppe with four treatments: no grazing (NG), light (LG), moderate (MG), and heavy grazing (HG). Aggregate characteristics were assessed across four soil layers (topsoil: 0–10 cm, midsoil: 10–30 cm, subsoil: 30–40 cm, Whole soil: 0–40 cm) using dry- and wet-sieving. Results showed that dry-sieved aggregate size distribution was more sensitive to grazing than wet-sieved aggregates. HG dry-sieved >2 mm aggregates significantly increased by 4.98% in whole soil, with MG and HG enhancing large aggregates in topsoil (5.80% and 6.31%, respectively), while LG and MG < 0.25 mm aggregates increased by 8.28% and 11.01%, respectively, in the subsoil. HG had no significant effect on subsoil <0.25 mm aggregates. Aggregate stability was highest under HG, particularly in the subsoil, where both mechanical and water stability were significantly improved 0.14 mm and 0.32 mm, respectively. Soil aggregate stability varied notably with soil depth. Mechanical stability consistently increased with depth, irrespective of grazing intensity. In contrast, water stability displayed distinct patterns among treatments: a progressive increase with depth under NG, a topsoil minimum under LG and MG, and relatively constant values across depths under HG. Soil aggregate stability was jointly regulated by grazing intensity coupled with soil depth, significantly influenced by soil bulk density, microbial biomass carbon, and belowground biomass. Although higher grazing intensity can improve aggregate stability, it may also have adverse effects on soil porosity, bulk density, and belowground biomass. Thus, intermediate grazing is critical for maintaining aggregate stability and the long-term sustainability of typical steppe ecosystems.